Ethical Issues in Cardiac Surgery - Kavarana, Minoo N. (2012)
While ethical behavior has always been part of cardiac surgical practice, ethical deliberation has only recently become an important component of cardiac surgical practice. Issues such as informed consent, conflict of interest, and professional self-regulation, among many others, have increasingly attracted the attention of cardiac surgeons. This review covers several broad topics of interest to cardiac surgeons and cardiologists, and treats several other topics more briefly. There is much uncertainty about what the future holds for cardiac surgical practice, research, and culture, and we discuss the background of ethical issues to serve as a platform for envisioning what is to come.